Meaning of Being Siri Wife in a Poligamous Marriage - Nisa, Mufidatunnisa; Jendrius; Indraddin (UNIB Press, 2025)
Second wives in siri polygamous marriages frequently face a legal inequality, social stigma, and cultural pressure. Interestingly, many siri wives do not necessarily perceive their position negatively. On the contrary, they are able to construct positive meanings through their experiences and social interactions. This study aims to identify the meanings constructed by siri wives regarding their position in polygamous marriages, and analyze the adaptive strategies developed by siri wives. This research employs a qualitative approach with data collected through in-depth interviews. The informants consist of five second siri wives. Data analysis was conducted using the Symbolic Interactionism theory by George Herbert Mead. The findings show that siri marriages are perceived as a form of social status recognition, a source of emotional and financial security, and a symbol of the husbands commitment. The status of a siri wife is also seen as a means of gaining affection, escaping loneliness, and attaining flexibility in roles and time. Children born from siri marriages are regarded as a core part of family identity and a primary reason to remain in the marriage. Adaptive strategies include financial independence, emotional detachment from stigma, social participation, and maintaining proper appearance. It is concluded that siri wives construct the meaning of their status not merely based on legal recognition or societal judgment, but through social interaction, self-awareness, and creative negotiation of their position within the reality of polygamous marriage.